Frozen-Dried Human Cord Blood Leukoconcentrate as Correcting Agent of Immune Status when Treating Atopic Dermatitis (Experimental Study) - Tarannik, Anna K.; Ostankova, Lyudmila V.; Grisha, Igor G.; Sokol, Larisa V.; Lutsenko, Elena D.; Bondarovich, Nikolay A.; Ostankov, Maksim V.; Goltsev, Anatoliy N. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):165.